2017
DOI: 10.1016/j.jcin.2017.06.058
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention of Chronic Total Occlusions in Patients With Low Left Ventricular Ejection Fraction

Abstract: In CTO patients with low LVEF, PCI could represent a safe and effective revascularization strategy achieving good midterm outcome and LVEF improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
58
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 37 publications
11
58
1
4
Order By: Relevance
“…Regarding our baseline demographic characteristics, CTO patients with low LVEF were more diabetic and affected by CKD, when compared to those with preserved and mid‐range LVEF. This was concordant with Galassi et al & Tajstra et al, who revealed that patients with CTO and low LVEF had a higher prevalence of diabetes, peripheral vascular disease (PVD), and CKD besides a higher frequency of previous myocardial infarction (MI), and higher percentage of multivessel coronary artery disease (CAD).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding our baseline demographic characteristics, CTO patients with low LVEF were more diabetic and affected by CKD, when compared to those with preserved and mid‐range LVEF. This was concordant with Galassi et al & Tajstra et al, who revealed that patients with CTO and low LVEF had a higher prevalence of diabetes, peripheral vascular disease (PVD), and CKD besides a higher frequency of previous myocardial infarction (MI), and higher percentage of multivessel coronary artery disease (CAD).…”
Section: Discussionsupporting
confidence: 89%
“…Fifth, the assessment of angina status was not performed in accordance with standardised measures, such as Seattle Angina Questionnaire, thus making cross-trial comparisons difficult, although the finding of a reduced symptom burden coincides with previous studies,6 including the recent presentation of the preliminary results of the randomised EURO CTO trial i .…”
mentioning
confidence: 79%
“…In summary, the EXPLORE trial, although overall neutral, seems to further broaden the evidence base and may, together with other recent CTO studies, which have established the potential of CTO PCI to improve quality of life and reduce symptoms,6 warrant further inquiry by applying the increasingly efficient and safe technique of CTO PCI in different clinical settings, with the ultimate goal of using what seems to be a clinically intuitive benefit of percutaneous complete revascularisation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…As evidenced by recent trials, CTO PCI success is improving, but patient selection is key.There has been much interest in CTO PCI in patients with low left ventricular ejection volume (LVEF). Galassi conducted a prospective, multicenter trial of 839 patients undergoing elective CTO PCI comparing three groups: LVEF >50%, LVEF 35-50%, and LVEF <35% 45. All groups had comparable success rates above 90% with low EF not being a predictor of CTO failure.…”
mentioning
confidence: 99%